DAYA TAHAN ALAMI 30 JENIS KAYU TERHADAP RA YAP TANAH Macrotermes gilvus (Hagen); SUATU UJI LAPANG YANG DIPERCEPAT - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1995)
Two bundles  of  wood  samples  consisting  of  each thirty  wood  species  were  exposed  to subterranean termite Macrotermes  gilvus   (Hagen) for 14 weeks (3.5 months) in a rural area of Cikampek and in  an arboretum  of the  Centre for  Forest  and Natural  Conservation Research and Development located in  Janlapa,  Bogor.  To accelerate the termite attack,  a piece  of corru- gated paper  was inserted in each layer of wood arrangements in the bundles. in Cikampek, the wood samples were directly exposed to an active colony of the termite species.  Meanwhile, in  Jalanpa such test method was not conducted because the experiment formerly was not designated to this termite   species.  Thus,  the attack by  this termite species  was probably  occured by chance only.the  result of the experiment showed that, excepl the damage degree,  there was no significant difference in the pauern  of termite attack between the test samples exposed in the two locations. Here,  most stake tests exposed in Cikampek   were more severely infested than those in Jalanpa. From the two test sites,   it can be concluded that aboui 37%   (Aglaia versteeghii ,   Hopea odorata, Khaya  anthothcca,   Mimusop   elingi,   Neonauclea   spec,   Planchonia   valida,  Quercus  turbinata, Eucalyptus  urophylla,   Eugenia  lincata,   E.   polyantha,   and Podocarpus  blumei,  13%   (Altingia excelsa, Castanopsis javanica,  Shorea seminis,  Swintonia glauca),  20%  (Calophyllum inophyllum, Dacrydium becarii,  Gluta walichii,  Heritiera javanica,  Peronema canescens,  and Shorea platy- clados),   23   %   (Agathis philippinensis,  Anthocephalus  cadamba,  Anthocephalus spec.,   Eucalyptus alba,   Gluta renghas,   G,   rostrata,  Shorea  meristopteryx.),   and  7  %  (Elaeocarpus  sphaericus; Laplacea subintegerrima)  might be respectively classified highly resistant, resistant,  moderately resistant,  less resistant,  and perishable  to the termite attack.